Clinical significance of platelet-associated hematological parameters as an early supplementary diagnostic tool for sepsis in thrombocytopenic very-low-birth-weight infants. (3rd October 2015) - Kim, Ju Yeon; Yoon, Jeongah; Lim, Chae Seung; Choi, Byung Min; Yoon, Soo-Young
Abstract: Sepsis is an important cause of death in very-low-birth-weight (VLBW) neonates. Although conventional diagnostic indicator of sepsis has been done by blood cultures, this took much longer time. The measurement of platelet-associated parameters such as mean platelet volume (MPV) and platelet distribution width (PDW) become more reliable and accurate parameters as a non-specific marker for sepsis. Our objective is to examine the usefulness of those platelet hematological parameters as a supplementary diagnostic tool for sepsis in VLBW infants. This study is a retrospective cohort study of neonates subject to the diagnosis of sepsis from October 2006 to July 2010. This study was conducted at Korea University medical center. We studied total 2, 336 infants for 32 days from birth (Day 0) to Day 31. We compared three groups of infants to examine differences of platelet parameters according to their age from birth to Day 31: (i) full-terms versus VLBW without sepsis, (ii) VLBW without sepsis versus VLBW with sepsis and (iii) thrombocytopenic VLBW without sepsis versus those with sepsis. The platelet-associated parameters were significantly distinguishable between septic and non-septic groups at their early age (∼1 week), especially platelet counts (PLT) ( p = 0.0091), MPV ( p = 0.007) and PDW ( p = 0.0372) in thrombocytopenic VLBW infants. The decreased PLT, elevated MPV and PDW were major characteristics of septic group. We suggested maximum cutoff values of the platelet factors by performing receiver operating characteristic curve analysis between septic and non-septic thrombocytopenic VLBW infants, among which MPV was the most promising index (AUCMPV = 0.7044 > AUCPLT = 0.6921 > AUCPDW = 0.6593). Platelet-associated hematological parameters are useful for the early diagnosis of sepsis as a more efficient and supplementary diagnostic method in thrombocytopenic VLBW infants.